The Influence of Quantum Teaching Learning Approach on Science Activities of Elementary School Students - Arisma Dyah Nurmalisa; Syarifuddin Kune; Evi Ristiana (Pedagogik Journal of Islamic Elementary School, 2022)
This study aimed to determine the effect of the quantum teaching approach on student learning activities on homogeneous and heterogeneous mixed materials. This study uses a quasi-experimental design method. The research design used in this study is a non-equivalent control group design. The population in this study were all students of class VA and VB, as many as 62 students, while the sample in this study was class VA as the experimental class, as many as 30 students and class VB, as many as 32 students. They collected data using observation sheets, test sheets, and documentation—analysis of student learning activity data using the percentage formula and t-test. The results of data analysis show that the average student learning activity in the experimental class using the quantum teaching approach is classified as very active with a percentage value of 81%, and the average student learning activity in the control class with a conventional learning approach is classified as active with a percentage value of 72%. Thus, it can be concluded that the quantum teaching approach has a significant influence on science learning activities with homogeneous and heterogeneous mixed concepts for class V of the Mandai State Elementary School, Makassar City.